Epidemiology of Hypoxic Community-Acquired Pneumonia in Children Under 5 Years of Age: An Observational Study in Northern India - Awasthi, Shally; Rastogi, Tuhina; Pandey, Anuj Kumar; Roy, Chittaranjan; Mishra, Kripanath; Verma, Neelam; Kumar, Chandra Bhushan; Jain, Pankaj Kumar; Yadav, Rajesh; Chauhan, Abhishek; Mohindra, Namita; Shukla, Ram Chandra; et al. (Frontiers in Pediatrics, 2022)
Background Community acquired pneumonia (CAP) is the leading cause of under-five mortality in India. An increased risk of mortality has been reported in cases of hypoxic pneumonia. Methods Primary objective of this study was to assess the proportion of children aged 2-59 months, hospitalized with hypoxic CAP as well as socio-demographic, clinical and radiological features associated with it. Secondary objective was to determine the risk of mortality among hospitalized cases of hypoxic CAP. This prospective, observational study was conducted in four districts of Northern India, between January 2015 to April 2021. A hospital-based surveillance network was established. Inclusion criteria was: (a) child between 2-59 months (b) hospitalization with symptoms of WHO-defined CAP (c) resident of project-district (d) illness of <14 days (e) child had neither been hospitalized for this illness nor recruited previously. Children whose chest x-rays (CXRs) were either unavailable/un-interpretable and those that received any dose of pneumococcal conjugate vaccine-13 were excluded. Hypoxic pneumonia was defined as oxygen saturation<90% on pulse oximetry or requiring oxygen supplementation during hospital stay. Results During the study period, 71.9% (7196/10006) children of pneumonia were defined as severe, of which 35.9% (2580/7196) were having hypoxic pneumonia. Female gender and use of biomass fuel for cooking increased the odds of hypoxic CAP. Clinical factors like wheezing, pallor, tachypnea, low pulse volume, presence of co-morbidity, general danger signs, severe malnutrition as well as radiological factor of primary end-point pneumonia ± other infiltrates (PEP+OI) also increased the odds of hypoxic CAP in a conditional logistic regression model. Adjusted odds ratio for mortality with hypoxia was 2.36 (95% CI: 1.42-3.92), controlling for age (2-11 months), gender, biomass fuel for cooking, tachypnea, co-morbidities, low pulse volume, severe malnutrition and CXR findings. Conclusion: Almost one-third of cases hospitalized with severe CAP had hypoxia, which increased chances of mortality. Besides the known danger signs, certain newer clinical signs such as pallor and wheezing as well as PEP+OI are associated with hypoxic CAP. Therefore, objective assessment of oxygen saturation must be done by pulse oximetry in all cases of CAP at the time of diagnosis.